Auditoría financiera y su incidencia en los resultados económicos de la agrícola bananera El Esfuerzo, cantón Valencia, año 2013 - Pico Quinto, Paola Alexandra (2015)
The financial audit examines the financial statements and through them the financial operations performed by the entity, in order to issue a technical and professional opinion based on legal provisions that regulate the business activities of the companies on the reliability or not of the figures shown in the financial statements, summarizing its economic development occurred during a given period, the research was conducted at the Agricultural Banana The effort, which is principally engaged in planting, cultivation and production of bananas for export, and located on the campus of San Pablo Valencia Canton 12 km from the entrance to Zapote; Financial statements at December 31, 2013, the Internal Control procedures by COSO I method and application of Financial Ratios to determine the incidence of economic performance in the state was examined, this information is the responsibility of management and my responsibility is to express an opinion on the financial statements; the recommendations arising from the enforcement made to the financial statements and procedures performed in the period ended December 31, 2013 by the tests; in which the following results were obtained; with respect to risk audit the following results, inherent risk is 28%, detection risk 10%, control risk 15.2% so the audit risk calculated was 0.42% considered under acceptable, however the make deep tests revealed that the company does not reflect value in the inventory account so it is recommended that has a value is recorded as the company if you own a winery where you store your supplies and materials for production and these are part inventory.